Clusters of polymersomes and Janus nanoparticles hierarchically self-organized and controlled by DNA hybridization. (February 2023) - Mihali, Voichita; Skowicki, Michal; Messmer, Daniel; Palivan, Cornelia G.
Abstract: The combination of "hard", structurally well-defined particles with "soft", functional compartments bears great potential to produce structurally intricate hybrid nanomaterials that promote a multitude of applications that require multimodal agents and that permit the production of molecular factories. However, the co-assembly of "hard" and "soft" components in a programmable and directional manner is challenging due to the strongly differing mechanical properties of such disparate entities. Here, a versatile strategy to generate clusters by the directional and controlled self-organization of "hard" Janus nanoparticles (JNPs) with "soft" polymersomes is described. The hybridization of complementary ssDNA strands bound to the components drives cluster formation, while the asymmetry of the JNPs governs the directionality of the self-organization. Various factors have been explored to simultaneously preserve the integrity of the polymersomes and program the cluster formation. Differently loaded polymersomes on each lobe of the JNPs preserved their architecture in the clusters which, were shown to be non-toxic when interacting with cell lines. The architecture of the clusters, as a molecular factory where each component can be separately controlled bears great promise for use in advanced medical applications, including theranostics and correlative imaging. Graphical Abstract: ga1 Highlights: Polymersomes and heterofunctional Janus nanoparticles are assembled into well-defined hybrid clusters. Directional self-organization mediated by ssDNA overcomes challenges in co-assembling hard and soft components. Directionality of self-organization render the cluster preparation programmable and modular in composition and function. The hybrid clusters are shown to be biocompatible, interacting strongly with cell surfaces. Prospective applications include correlative imaging, reaction cascades, and nanotheranostics.